Pemberdayaan Remaja Putri Melalui Edukasi dan Pelaporan Konsumsi Tablet Tambah Darah Berbasis Aplikasi Care Dalam Menangani Kejadian Anemia - Nur, Muhammad Purqan; Dwiyana, Asnurbaety; Suwardoyo, Untung; Nasriani, Nasriani; Nisma, Nismawati Natsir; Rusman, Ayu Dwi Putri (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2024)
Anemia is a significant health problem among adolescent girls, mainly due to increased iron demand during growth and menstruation. SKI data in 2023 states that the prevalence of teenage anemia is 21%. This service aims to reduce the prevalence of anemia in adolescent girls through the socialization of the CARE Application (Prevent Teenage Anemia) and the provision of blood supplement tablets at MTsN Pangkep. This activity involved 60 female students as participants, with methods that included health education through videos, hemoglobin checks, anthropometric measurements (weight, height, upper arm circumference), and distribution of blood supplement tablets by the local Puskesmas. The community service team acted as facilitators, with support from UKS teachers and Puskesmas health workers. The results showed that the structured and collaborative approach effectively increased understanding of anemia and improved adolescent girls' health status. The activity also strengthened health literacy among participants, which may contribute to a long-term reduction in anemia prevalence. In conclusion, multifaceted interventions that combine health education and nutritional supplementation are essential in preventing anemia in adolescent girls and need to be implemented more widely in other school settings to achieve a more significant impact.